PENGARUH APLIKASI METODE CARD SORT TERHADAP AKTIVITAS DAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS VII SMP NEGERI 2 KOTA PAGARALAM - Wita Ariani (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: The problems of this study were 1. “ Is There any diffrences in students learning activities between the students who are though through Sort Card and Those who are not ? “ 2. Is There any differences in students learning result between the students Who are tough through sort Card and those who are not to the seventh grade students of SMP N 2 Pagaralam ? . The Objective of the study was to know how the Incerease of seventh grade students activity and learning result on Islamic Religion education at SMP N 2 Pagaralam by using Sort Card . The Method of this Study was experimental research by using quantitative approach as the method that is use to search the influence of a specific threatment to another in controlled condition which purpose was to know the descrption whether or not there is defferences between the students who are tough through Sort Card and those who are not. Besides to improve the syistem, ways of work, material process and competence or learning situation. The technigve of collecting the data of this research were observation to know students activity and written test to know students learning result. After conducting the research, the writter found that VII. C as experimental class which was use Sort Card had good activity that could be seen in student activity averange result which reached ( 77,85 ) whetter VII. E as controlled class which was not use Sort Card got ( 59,3 ), While learning result could be seen by the student written test result and Experimental class averange was ( 77,84 ) and the controlled class was ( 72,80 ). It means that Sort Card method can increase students activity and learning result on islamic religion education at SMP N 2 Pagaralam Negeri 2 Kota Pagaralam.